Keto-adaptation and endurance exercise capacity, fatigue recovery, and exercise-induced muscle and organ damage prevention: A narrative review - Ma, S.; Suzuki, K. (Sports, 2019)
A ketogenic diet (KD) could induce nutritional ketosis. Over time, the body will acclimate to use ketone bodies as a primary fuel to achieve keto-adaptation. Keto-adaptation may provide a consistent and fast energy supply, thus improving exercise performance and capacity. With its anti-inflammatory and anti-oxidative properties, a KD may contribute to muscle health, thus preventing exercise-induced fatigue and damage. Given the solid basis of its potential to improve exercise capacity, numerous investigations into KD and exercise have been carried out in recent years. This narrative review aims to summarize recent research about the potential of a KD as a nutritional approach during endurance exercise, focusing on endurance capacity, recovery from fatigue, and the prevention of exhaustive exercise-induced muscle and organ damage.